2006
DOI: 10.1242/jcs.02934
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiitriggers Gi-dependent PI 3-kinase signaling required for inhibition of host cell apoptosis

Abstract: Infection with the intracellular parasite Toxoplasma gondii renders cells resistant to multiple pro-apoptotic signals, but underlying mechanisms have not been delineated. The phosphoinositide 3-kinase (PI 3-kinase) pathway and the immediate downstream effector protein kinase B (PKB/Akt) play important roles in cell survival and apoptosis inhibition. Here, we show that Toxoplasma infection of mouse macrophages activates PKB/Akt in vivo and in vitro. In a mixed population of infected and non-infected macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 61 publications
5
88
0
Order By: Relevance
“…However, a GiPCR signaling pathway seems to play a crucial role in the migratory phenotype [116]. This observation provides a potential mechanistic link to the previous report that T. gondii modulation of the GiPCR signaling pathway is involved in maintaining the host cells in an anti-apoptotic state [113].…”
Section: Manipulation Of Host Cell Motility and Migrationsupporting
confidence: 72%
See 2 more Smart Citations
“…However, a GiPCR signaling pathway seems to play a crucial role in the migratory phenotype [116]. This observation provides a potential mechanistic link to the previous report that T. gondii modulation of the GiPCR signaling pathway is involved in maintaining the host cells in an anti-apoptotic state [113].…”
Section: Manipulation Of Host Cell Motility and Migrationsupporting
confidence: 72%
“…The Akt/ PKB activity is linked with the promotion of the NF-κB pathway [112]. Infection of mice with T. gondii leads to the increase of the phosphorylation of Akt/PKB in macrophages containing parasites [113]. In vitro experiments reveal that the levels of activated PKB, MEK1/2 and Erk1/2 are increased in macrophages and splenic cells infected with T. gondii in a manner dependant upon the PI3K and Gi protein-coupled transmembrane receptors (GiPCR) ( Figure 2).…”
Section: Role Of the Pi3k Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the effectiveness of the toxin by examining activation of protein kinase B (PKB) that depends on G i protein signaling during RH infection ( Fig. 2C) (41).…”
Section: Parasite Il-12 Induction In Bone Marrow-derived Macrophages supporting
confidence: 53%
“…Toxoplasma gondii activates PI3-kinase through the signal pathway transmitted by the heterotrimer of Gi protein, resulting in the phosphorylation of PKB/Akt and ERK1/2 MAPK. Both in vitro and in vivo experiments have demonstrated that after mouse phagocytes are infected by T. gondii, the PKB/Akt pathway is activated, and the induction of apoptosis in infected macrophages is prevented (Kim and Denkers, 2006).…”
Section: The Host Cell Is Exploited By T Gondii To Establish An Invamentioning
confidence: 99%